Financial dependence and growth: diminishing returns to improvement in financial development - Shen, Leilei (My University, 2013)
This paper examines how much financial development facilitates economic growth by nonparametrically estimating the e ffect of fi nancial development on reducing the costs of external fi nance to fi rms. The data reveal substantial evidence of diminishing returns to improvement in financial development.
Keywords: Financial dependence; Growth; Semiparametric estimation